Comparing Traditional and Digitized Cognitive Tests Used in Standard Clinical Evaluation – A Study of the Digital Application Minnemera - Björngrim, Stina; van den Hurk, Wobbie; Betancort, Moises; Machado, Alejandra; Lindau, Maria (Frontiers in Psychology, 2019)
The purpose of this study was to compare a new digitized cognitive test battery, Minnemera, with its correspondent traditional paper-based cognitive tests. Eighty-one healthy adults between the ages of 21 and 85 participated in the study. Participants performed the two different test versions (traditional paper-based and digitized) with an interval of four weeks between the tests. Test presentation (the order of the test versions presented) was counterbalanced in order to control for any possible test learning effects. The digitized tests were constructed so that there were only minor differences when compared to the traditional paper-based tests. Test results from the paper-based and digitized versions of the cognitive screening were compared within individuals by means of a correlation analysis and equivalence tests. The effects of demographic variables (age, gender and level of education) and test presentation were explored for each test measure and each test version through linear regression models. For each test measure, a significant correlation between traditional and digitized version was observed ranging between r=.34 and r=.67 with a median of r=.53 (corresponding to a large effect size). Score equivalence was observed for four out of six tests. In line with previous traditional cognitive studies, age was found to be the most prominent predictor of performance in all digitized tests, with younger participants performing better than older adults. Gender was the second strongest predictor, where women outperformed men in tests measuring verbal memory and mental flexibility; men performed better than women in visual memory tests. Finally, the educational level of the test subjects had a strong effect on executive functions, with a higher educational level linked to a better inhibition response. This study suggests that the tests in the Minnemera cognitive screening battery are acceptably comparable to the traditional paper-based counterparts.